Gender associated with the intention to choose a medical specialty in medical students: A cross-sectional study in 11 countries in Latin America - Ng-Sueng, Luis Fernando (2016)
The selection of a medical specialty has been associated with multiple factors, such as personal preferences, academic exposure, motivational factors and sociodemographic factors, such as gender. The number of women in the medical field has increased in recent years. In Latin America, we have not found any studies that explore this relationship.Secondary analysis of the Collaborative Working Group for the Research of Human Resources for Health (Red-LIRHUS) data; a multi-country project of students in their first year and fifth year of study, from 63 medical schools in 11 Latin American countries. All students who referred intention to choose a certain medical specialty were considered as participants.There is an association between the female gender and the intention to choose Obstetrics/ Gynecology, Pediatrics, Pediatric Surgery, Dermatology, and Oncology. We recommend conducting studies that consider other factors that can influence the choice of a medical specialty.